Determination of 6 flavonol glycosides in epimedium health wine by ultra-high performance liquid chromatography - SHI Hao, MAO Qiongli, HU Yang, LI Xianzhi, YANG Qiang, LI Qiang, XIONG Xiaotong, YAN Ling, ZHU Yan (Zhongguo niangzao)
A method for simultaneous determination of 6 flavonol glycosides (icariin, epimedin C, epimedin B, epimedin A, epimedin A1 and icariside II) in epimedium health wine was established by ultra-high performance liquid chromatography (UPLC). The samples were purified by HLB solid phase extraction column (200 mg/6 ml) after the ethanol was removed by evaporation, separated by Agilent ZORBAX Eclipse XDB-C18 (2.1 mm×150 mm, 1.8 μm) column with a gradient elution using acetonitrile-0.1% formic acid as mobile phase. The flow rate was 0.3 ml/min, the column temperature was 25 ℃, the injection volume was 2 μl, and the detection wavelength was 270 nm. The results showed that under these conditions, the 6 flavonol glucosides had good linear relationship in their mass concentration range (R2≥0.999 6), the limit of detection (LOD) was 0.004-0.011 mg/L, and the limit of quantitation (LOQ) was 0.013-0.034 mg/L. The average spiked recovery rates were 94.741%-99.713%, and the relative standard deviations (RSD) of precision, stability, repeatability and spiked recovery rates tests results were all lower than 3.0%. The method was sensitive, stable and accurate, and was suitable for the determination of 6 flavonol glycosides in epimedium health wine.